Political Revolt and Youth Unemployment in Tunisia Exploring the Education-Employment Mismatch - Schaefer, Isabel (Middle East Today, 2018)
This book discusses youth unemployment in post-revolutionary Tunisia, paying particular attention to the so-called skill mismatch. Youth unemployment was one of the major factors triggering the Tunisian revolution, and continues to be a central socio-economic challenge. The Tunisian labour market is marked by a strong increase of higher education graduates while the economic system is dominated by sectors mainly employing a less qualified labour force. This study investigates current labour market trends, and provides insights into the underlying causes of persisting high youth unemployment. The author argues that economic crisis, difficult political conditions since 2011, and inefficient labour market policies did not foster sufficient job creation, and that special attention needs to be paid to the educational causes of the skill mismatch in youth employment in future sustainable development models. .